Geoelectricity Data Analysis For Identification The Aquifer Configuration In Bandorasawetan, Cilimus, Kuningan, West Java Province - Alfadli, Muhammad Kurniawan; Natasia, Nanda (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Indonesian water consumption is influenced by the people growth. One of Water consumption fulfilment by groundwater aquifer. Bandorasawetan is one of the areas which predicted have proper potential due to located in East of Mt. Ceremai that predicted recharge area. Based on regional geological data, Bandorasawetan is an undifferentiated young volcanic product which consists of lava, breccia, lapilli, and tuffaceous sand. Geophysics method for groundwater prediction is 2-D geoelectrical with Wenner – Schlumberger configuration. The result of acquisition is obtained resistivity value from 0 - >1000 Ohm. m. Interpretation from data distribution is consist of two resistivity range that describes lithology on the research area, such as: 0 – 150 Ohm.m contributed as aquiqlud with tuffaceous sand lithology and > 150 Ohm.m interpreted as volcanic breccia lithology. Volcanic breccia has a role as aquifer in study area, the conclusion is distribution of resistivity value with range > 150 Ohm.m be the reference to developing groundwater resource in study area. Depth of aquifer is varying, deeper to the east. In Line – 1, depth of the aquifer is 48 meters and in Line – 2, depth of aquifer be 60 meters.